HISTORICAL BACKGROUND OF RAYALASEEMA - Vijaya Kumar Reddy, Mure (International Journal of Psychosocial Rehabilitation, 2020)
Rayalaseema districts was ruled by Nandas, Mouryas, Satavahanas, the Pallavas, Greater Pallavas of Kanchi, Chalukyas of Badami, Early Renadu Cholas, Later Renadu Cholas, the Rastrakutas, Banas, Early Vaidumbas, the Nolamba Pallavas, the Chalukyas of Kalyani, the Imperial Cholas, the Pandyas, the Yadavarayas, Yadavas, the Kakatiyas, the Reddis of Kondavidu, Vijayanagara rulers. In the 1799 battle, Tippu was defeated and died in the hands of the British and the Nizam got the territory. But the Nizam ceded the areas which he had acquired from Mysore under the treaties of 1792 and 1799 to the British in return for a subsidiary force. Thus the districts of Kurnool, Ballary, Anathapur and Cuddaph were handed over to the British. These districts were known as the Ceded Districts.